Xanthine Oxidase: Disposable Biosensor for Herbal Antioxidant Evaluation - Mohd Noor, Ahmad, Prof. Dr.; Rosnin, Mustaffa; Rafidah, Abd Rahman; Kwan, Wei Yen; Zhari, Ismail, Prof. Dr. (Malaysian Invention & Design Society (MINDS), 2010)
Prof. Dr. Mohd. Noor Ahmad and his team from School of Bioprocess won silver Xanthine Oxidase Disposable Biosensor for Herbal Antioxidant Evaluation. ITEX 2005, 19th - 21st May 2005 was held at Putra World Trade Centre (PWTC), Kuala Lumpur.